Study of Corrosion Behavior of Dicalcium Phosphate-dihydrate (DCPD) Coating Prepared by Large Amplitude Sinusoidal Voltammetry (LASV) Technique on ZW3 Magnesium Alloy. (2017) - Kajánek, Daniel; Pastorek, Filip; Fintová, Stanislava; Bača, Adrián
Abstract: This study is focused on corrosion behavior of dicalcium phosphate-dihydrate (DCPD) coating electrodeposited by large amplitude sinusoidal voltammetry (LASV) technique on ZW3 magnesium alloy in sodium sulphate solution. The electrochemical characteristics of coated and non-coated samples were evaluated by potentiodynamic polarization (PD) tests in 0.1 M Na2 SO4 solution at the temperature of 22±1 °C. The PD curves were analyzed using Tafel extrapolation method. The analyzed values of the corrosion potential and corrosion current density obtained from PD tests proved that DCPD coating can effectively increase corrosion resistance and slow down degradation of ZW3 magnesium alloy in chosen environment.